(untitled) (Journal of Misan Researches, 2024)
This study aims to investigate the impact of the guided imagination strategy on improving the performance of fourth-year literary students in the subject of history, with a focus on enhancing understanding and engagement with historical content through stimulating imagination and creative thinking. The researcher adopted an experimental design involving two groups: an experimental group and a control group. A total of 60 students from Al-Batool Secondary School in Maysan Governorate were selected, ensuring the experiment’s balance and generalizability. The students were evenly divided into two groups, with 30 students in each. The experimental group, consisting of 30 students, was taught using the guided imagination strategy, while the control group, also comprising 30 students, was taught using traditional methods. To measure the impact of the guided imagination strategies on students’ performance, the researcher employed an achievement test designed to assess understanding and analysis of historical concepts. Additionally, questionnaires were used to evaluate students’ engagement with the guided imagination sessions. The results revealed that students in the experimental group achieved significant improvement in their performance compared to the control group. This underscores the effectiveness of the guided imagination strategy in enhancing academic achievement and deep understanding of historical content, as well as its role in fostering curiosity and critical thinking. Based on these findings, the researcher recommended integrating the guided imagination strategy more widely into curricula, emphasizing the need to tailor educational sessions to accommodate the diverse learning styles of students. In conclusion, the study makes a valuable contribution to the field of history education by highlighting the active role of guided imagination in improving students’ performance and engagement with academic content. This approach not only boosts their academic achievement but also develops their creative and critical thinking skills.